Coping strategies in riverbank erosion affected areas: A case study of Andharmanik village in Manikganj district. - Rahman, Md. Abdur (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2022.